Penyakit Ginjal Kronis : apakah pola makan berbasis nabati efektif? - Kurniawan, Wawan; Hairunisa, Nany; Amarendra, Gerie (Fakultas Kedokteran Universitas Trisakti, 2023)
Chronic kidney disease (CKD) is a global problem whose number of sufferers is increasing. Various methods have been widely used to prevent worsening of kidney function. In addition to controlling causative factors, diet planning also plays a role in improving kidney function. Confining protein utilization has long been a foundation of wholesome treatment for patients with CKD. In any case, the suggested sum of dietary protein admissions may change between consensus. A vegan who eats less that's exceptionally low in protein has appeared to diminish the chance of kidney failure in patients with progressed CKD. These findings indicate that protein sources can also influence the improvement of kidney function. Dietary medications play a good part in the management of CKD and avoiding or postponing kidney replacement therapy. The study proposes that a plant-dominant low-protein diet (PLADO) of 0.6–0.8 g/kg/day composed of >50% plant-based sources, managed by nutritionists prepared in non-dialysis CKD care, is promising and reliable with the exactness diet. Plant-based Very low-protein diets may inhibit decreased eGFR (estimated glomerular filtration rate) and the need for renal replacement therapy. This literature review aims to find evidence about the effectiveness of plant-based diets in treating cases of chronic kidney failure.